2021
DOI: 10.1002/admt.202000985
|View full text |Cite
|
Sign up to set email alerts
|

Achieving High Power Density and Long‐Term Stable Flexible Triboelectric Nanogenerators through Surface Functionalization of High Work‐Function Electrode with Cationic Thiol‐Based Self‐Assembled Monolayer

Abstract: In this study, a reliable strategy is demonstrated to improve performance and stability of a triboelectric nanogenerator (TENG) by using cationic (11‐mercaptoundecyl)‐N,N,N‐trimethylammonium bromide (MUTAB) self‐assembled monolayer (SAM) as the surface modification layer for high work‐function (WF) Ag electrode. The thiol head group of MUTAB can form covalent bond to Ag surface, while the positively charged ammonium group can induce favorable surface dipole moment to lower the WF of Ag layer, enabling efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…Additionally, SAMs of substituted aliphatic molecules have been used to functionalize surfaces for triboelectric nanogenerators (TENG). 271 Recently, Cheng et al 272 used cationic thiol-based SAMs to effectively manipulate the work function of Au substrates, enabling efficient TENG output characteristic. In their previous work, the authors also used fluorinated aliphatic molecules with trichlorosilane termini group, which upon treatment, forms a robust SAM on a PDMS or Al surface, showing long-term stability and highest output performance of these SAM-based TENG devices.…”
Section: A Aliphatic Moleculesmentioning
confidence: 99%
“…Additionally, SAMs of substituted aliphatic molecules have been used to functionalize surfaces for triboelectric nanogenerators (TENG). 271 Recently, Cheng et al 272 used cationic thiol-based SAMs to effectively manipulate the work function of Au substrates, enabling efficient TENG output characteristic. In their previous work, the authors also used fluorinated aliphatic molecules with trichlorosilane termini group, which upon treatment, forms a robust SAM on a PDMS or Al surface, showing long-term stability and highest output performance of these SAM-based TENG devices.…”
Section: A Aliphatic Moleculesmentioning
confidence: 99%
“…28,29 SAMs are ordered assemblies of organic molecules which can be covalently linked to various oxide, metal and polymer surfaces. Different polymers have been employed as substrates for SAM functionalization, such as polydimethylsiloxane (PDMS) 30–32 and polyethylene terephthalate (PET). 32–34 Most often TENGs are constructed using both PDMS and metallic electrodes modified by SAMs as contact layers.…”
Section: Introductionmentioning
confidence: 99%
“…32 Notably, fluorine-terminated SAMs on PDMS in combination with an ammonium bromide terminated SAM on a Ag electrode reached a power density of 39.4 W m −2 . 30 Regarding TENGs using polymers as both contact layers, Shin et al demonstrated that a TENG reaching a power density of 55 W m −2 can be constructed using two differently modified PET contact layers – one with an amine-based SAM and the other with a halogen-based SAM. 33…”
Section: Introductionmentioning
confidence: 99%
“…11,17–21 For instance, we have demonstrated the feasibility of using self-assembled fluorinated molecules as the surface modification layer for PDMS, thereby significantly improving the TENG performance while maintaining excellent durability. 23–25 Despite this fact, TENGs based on existing surface modification layers are still mostly constrained by the rigid substrate. In addition, an adhesion problem between the triboelectric layer and the surface modification layer is usually observed.…”
Section: Introductionmentioning
confidence: 99%